Implementasi Pelatihan Memahat Dalam Kemandirian Masyarakat P3 (Pengamen, Pengemis, Pemulung) di Sanggar Pensi Kabupaten Bondowoso - Dia Ayu Patmawati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The P3 community (beggars, buskers and scavengers) in Bondowoso Regency causes the poverty rate in Bondowoso Regency to be quite high. The non governmental organization that supports the P3 community (beggars, buskers and scavengers) to be more empowered is the pensi studio which provides several trainings in the arts and creative economy, one of which is training in the art of sculpting which can change the independence of the P3 community (beggars, buskers and scavengers). Based on these conditions, this research aims to describe the implementation of sculpting training in the independence of the P3 community (buskers, beggars, scavengers) at Sanggar Pensi, Bondowoso Regency. This type of research uses descriptive qualitative research by determining the research location, namely using a purposive area technique which is located in Sanggar Pensi, Bondowoso Regency. The technique for determining research informants uses purposive sampling. Next, researchers used data collection techniques through interviews, observation and documentation. Then, to ensure the validity of the research data, the researcher used extended participation, diligent observation and triangulation, namely triangulation of sources and techniques. The final step is for the researcher to carry out data analysis by collecting data, reducing data, presenting data, and drawing conclusions. The research results show that in the implementation of sculpting training there are media, materials and learning methods that form emotional independence, economic independence, intellectual independence and social independence. This can be seen as individuals who are more independent, wise and harmonious, both in individual and social life, while making a real contribution to the preservation and empowerment of local culture
Reaploud Repository February 2026_Hasyim
Keywords: Implementation of training; independence; P3 community